Inflammatory epilepsy (FIRES) and haemophagocytic lymphohistiocytosis (HLH): an adult case. Issue 1 (31st January 2023) - Kam, Ian; Prentice, David; Kho, Lay Kun; Dharsono, Ferry
Abstract : We describe a man in his 30s with haemophagocytic lymphohistiocytosis (HLH), secondary to an upper respiratory tract infection, with subsequent febrile infection-related epilepsy syndrome. He had a prolonged hospital admission, during which he was treated with chemotherapy for HLH and antiepileptic medications for refractory seizures. He was discharged fully dependent to a care facility and died from aspiration pneumonia 11 months later. This case report highlights his management and discusses these conditions' pathophysiology and future management.